HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN BEROBAT PADA PENDERITA DIABETES MELLITUS TIPE 2 DI POLI ENDOKRIN BLU RSU Prof. Dr. R. D. KANDOU MANADO - Joice M. Laoh; Sri Indah Lestari; Maria Vonny H. Rumampuk (POLTEKKES KEMENKES MANADO, 2013)
The prevalence of Diabetes Mellitus in North Sulawesi ceached 8.1% well above the national rate of 5.7%, and Diabetes Mellitus patients who visit the Endocrine Poly BLU RSU Prof. Dr. R. D. Kandou Manado totaled 862 peoples. Family support represent one of the factor which influence patient ignoring in running treatment if medication. Patient compliance means that the patient and family have to spending a time in experiencing required treatment. Purpose of this research is to knowing the relationship of family support with medicines compliance of patient with Diabetes Mellitus in Poly of Endocrine of BLU RSU Prof. Dr. R. D. Kandou Manado. This research was executed with cross sectional method, sampleselection by using purposive sampling. Amount of sample are 100 responders. The instrument used was made by the researchers, in the from questionnaires. Data were analyzed by using computer assistance using the Fisher Exact TEST WITHSIGNIFICANCELEVEL (????= < 0.05). The result f this research indicate that good family support counted 88 peoples (88.0%) while less support 1 peoples (12.0%). For the medicines compliance of patient with diabetes mellitus in obedient category counted 87 people (87.0%) and is not obedient 13 people (13.0%). From statistic test result with the value of Significance (P) = 0.001 smaller than (????) 0.05, thusH1 is accepted and H0 is rejected. Concluded in this research there were between family support with the medicines compliance of patient with diabetes mellitus. Suggested these result can provide input for Endocrine of BLU RSU Prof. Dr. R. D. Kandou Manado